Report on the Technical Assistance Evaluation Mission to Transition Economies : Albania and Georgia. (Policy Papers; Policy Paper, 2011)
This evaluation of technical assistance (TA) and training in statistics looks at the experience of two transition economies, Albania and Georgia, during roughly the period 2005-2010. The TA, including the training, to these countries covered all the topical areas on which the IMF's Statistics Department's (STA) focuses, id est, national accounts, price statistics, and monetary, balance of payments and government finance statistics, albeit with differing emphases between the two countries. Part of the assistance was funded directly from the IMF's budget, while other elements (in particular the peripatetic advisors) were financed externally, in these cases by the Japanese government.